Proyecto de inversión para la creación de una empresa de alquiler de equipos náuticos en las playas de Buenaventura- Valle del Cauca (2013)
Our business idea aims to formulate an investment project for the creation of a company dedicated to providing rental services nautical equipment on the Buenaventura - Valle del Caucabeaches, which aims to cater to tourists and themselves places having tourist profile and intend to develop nautical recreation where water games will be made as the worm, aquatic bicycle, jet skiing, extreme sports like paragliding maritime, waterways parasailing to name a few, excellent and relaxing activities for Sharing family. Providing service equipment rental yachts with quality, efficiency, and in order to anticipate the needs of our users. This project allows us to analyze descriptive variables, such as age, sex, educational level, preferences, tastes, socio economic stratum, margin payment for services, and frequencyof use. Variables determinants for dissection. The project presented here is composed of statistical information, such as Buenaventura Chamber of Commerce and some websites as www.soydebuenaventura.com including serving us much information, too careful market research and use financial analysis to demonstrate that the development of nautical tourism on Buenaventura beaches is a competitive opportunity to lead a service that contributes to tourism and economic development of Buenaventura. This project is based primarily on the provision of water sports equipment rentals on the Buenaventura - Valle del Caucabeaches, which aims to meet national,international tourists is a project which is part of the line of business development for plans to contribute to the development of this sector in the region and the District as such and the nation, operating in synchrony with the development plans and competitive to competition at national level, such as departmental and municipal. The tourism is one of the most dynamic economies, the project is presented with the need to take this factor, generating dynamic activities currently provided at the District through the implementation of the company nautical equipment. Above, allow investors to have solid arguments about the project. Recreation such as cross- concept in this project presents different theorists, these regard, Butler (1969) says that recreation is a vital force that influences the lives of people, is essential to the happiness and satisfaction of the existence, and that through these activities the individual grows, develops their ability and personality. Recreation and isn`t a specific place, much less a group or geographic region, is of everyone because aspire to achieve wellness in the course of their lives.